The Covid-19 Situation - Singh, Dr Neena (Qualitative and Quantitative Methods in Libraries; 2020: Special issue : COVID-19 and the Libraries : the impact of, 2021)
The covid-19 crises has also brought new dimension, change in life style and work flow of people which is likely to remain a reality and part of our lives for some time, therefore addressing physical distancing, personal hygiene, and working in  protected environment is going to be an important activity for libraries in days to come. The paper discusses impact of changed situation on libraries and  digital transformations, increased digital activity, expanding online services, creating awareness on freely available digital content and remote accessibility. The paper also discusses the need for information literacy skills, and dealing with fake news/information, while researchers are working remotely and teaching activities moved to e-learning platforms and distance learning, the support of libraries through digital resources is inevitable. The paper further looks into some of the challenges and how these can be transformed into opportunities to add new paradigm and  bring innovative services in digital environment with special reference to Indian libraries. The author also highlights that Covid-19  pandemic  like situation has given some crucial lessons for libraries to learn, like have plans and  preparedness to handle library services from remote locations, have rich digital collection, dedicated web pages and good access to online platforms.